Asymmetric openness-growth nexus in 20 highly open OIC countries: Evidence from quantile-on-quantile regression approach - Ali, Sajid; Yusop, Zulkornain; Kaliappan, Shivee Ranjanee; Chin, Lee; Nazar, Raima (Taylor and Francis, 2021)
This study analyzes the asymmetric association between trade openness and economic growth in 20 highly open Organization of Islamic Cooperation (OIC) countries. A novel technique, quantile-on-quantile (QQ), is applied by using the data for the period 1991–2018. The results consider the mode of how quantiles of trade openness asymmetrically affect the quantiles of economic growth by giving an appropriate framework to apprehend the overall dependence structure. A positive linkage between trade openness and economic growth is found in United Arab Emirates, Malaysia, Suriname, Kuwait, Mauritania, Turkey, Tunisia, Qatar, Brunei, Morocco, Sierra Leone, Bahrain, Libya, Oman, Saudi Arabia and Albania. However, there is a negative association between trade openness and economic growth in Guinea, Guyana and Mozambique. Hence 16 out of 20 OIC countries support the trade-led growth hypothesis. These outcomes intimate that the intensity of asymmetric association in openness-growth nexus varies with countries that require individual attention and caution for governments in postulating the policies related to trade and growth.